2015
DOI: 10.1016/j.molp.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Loss of GSNOR1 Function Leads to Compromised Auxin Signaling and Polar Auxin Transport

Abstract: Cross talk between phytohormones, nitric oxide (NO), and auxin has been implicated in the control of plant growth and development. Two recent reports indicate that NO promoted auxin signaling but inhibited auxin transport probably through S-nitrosylation. However, genetic evidence for the effect of S-nitrosylation on auxin physiology has been lacking. In this study, we used a genetic approach to understand the broader role of S-nitrosylation in auxin physiology in Arabidopsis. We compared auxin signaling and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 124 publications
(184 reference statements)
10
54
0
Order By: Relevance
“…However, we also found that high concentrations of La result in remarkable cell death in PR tips. The meristematic cell division potential and stem cell niche activity, two main factors that affected root growth (Baluska et al , 2010; Liu et al , 2015), were markedly repressed and almost completely lost after 2 d of La treatment. Both the SHR / SCR pathway and the PLT pathway are involved in WOX5 -mediated QC identity (Aida et al , 2004; Blilou et al , 2005; Grieneisen et al , 2007; Galinha et al , 2007; Dinneny and Benfey, 2008; Ding and Friml, 2010; Zhao et al , 2014; Ji et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we also found that high concentrations of La result in remarkable cell death in PR tips. The meristematic cell division potential and stem cell niche activity, two main factors that affected root growth (Baluska et al , 2010; Liu et al , 2015), were markedly repressed and almost completely lost after 2 d of La treatment. Both the SHR / SCR pathway and the PLT pathway are involved in WOX5 -mediated QC identity (Aida et al , 2004; Blilou et al , 2005; Grieneisen et al , 2007; Galinha et al , 2007; Dinneny and Benfey, 2008; Ding and Friml, 2010; Zhao et al , 2014; Ji et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Five-day-old Arabidopsis seedlings were exposed to 150 μM La(NO 3 ) 3 for 2 d, and the root IAA content was quantified according to Gao et al (2014) and Liu et al (2015). Approximately 0.1 g (fresh weight) of roots was collected and immediately frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, GSNOR itself is a cysteine rich protein that is S-nitrosated by GSNO, which in turn initiates a feedback loop that affects GSNOR expression (Guerra et al, 2016) and activity (Brown-Steinke et al, 2010). Although it is beyond the scope of this review, it should be noted that GSNOR dysregulation in plants can result in significant biotic and abiotic nitrosative events that affect growth, development, and survival (Leterrier et al, 2011; Shi et al, 2015; Yun et al, 2016). …”
Section: Gsnor: Health and Diseasementioning
confidence: 99%
“…The AUXIN1/LIKE AUX1 (AUX1/LAX) family and the efflux carriers of the PINFORMED (PIN) family are required for optimal auxin distribution in root tips by regulating polar auxin transport (PAT) and are vital for modulating root growth and development (Laskowski et al, 2008; Yuan et al, 2013; Li et al, 2015; Shi et al, 2015). Mutations in these carrier genes result in dramatic defects in the root system architecture (RSA) (Laskowski et al, 2008; Shi et al, 2015). The Aux/IAA proteins are the negative regulators of auxin signaling (Ouellet et al, 2001).…”
Section: Introductionmentioning
confidence: 99%